Effect of Process Parameters on Nano-Microparticle Formation During Supercritical Antisolvent Process Using Mixed Solvent: Application for Enhanced Dissolution and Oral Bioavailability of Telmisartan Through Particle-Size Control Based on Experimental Design - Eun-Sol Ha; Heejun Park; Ji-Su Jeong; Seon-Kwang Lee; Hui-Taek Kang; In-hwan Baek; Min-Soo Kim (Pharmaceutics)
Background/Objectives: This study investigates the impact of supercritical antisolvent (SAS) process parameters on the particle formation of telmisartan, a poorly water-soluble drug. Methods: A fractional factorial design was employed to examine the influence of the SAS process parameters, including solvent ratio, drug solution concentration, temperature, pressure, injection rate of drug solution, and CO₂ flow rate, on particle formation. Solid-state characterizations of the SAS process particles using XRD and FT-IR confirmed their amorphous nature. The effect of particle size on the kinetic solubility, dissolution, and oral bioavailability of telmisartan was also assessed. Results: Using a mixture of dichloromethane and methanol, telmisartan amorphous nano-microparticles with sizes between 200 and 2000 nm were produced. The key parameters, particularly drug solution concentration and temperature, significantly affected the particle size. Interestingly, the ratio of the solvent mixture also had a significant effect on the particle morphology. Further experiments were performed to determine the conditions for preparing telmisartan amorphous nano-microparticles with various sizes by controlling the solvent mixture ratio and the concentration of the drug solution. It was revealed that a reduction in the amorphous particle size enhanced both the kinetic solubility and dissolution rates, leading to a significantly increased in vivo oral bioavailability in rats compared to unprocessed telmisartan. Conclusions: These findings suggest that SAS processing, utilizing adjustments of process parameters, offers an effective strategy for enhancing the bioavailability of poorly soluble drugs by generating amorphous spherical nano-microparticles with optimized particle size.